2017
DOI: 10.1080/15348458.2016.1277725
|View full text |Cite
|
Sign up to set email alerts
|

From Deficit to Asset: Locating Discursive Resistance in a Refugee-Background Student’s Written and Oral Narrative

Abstract: This article examines how a refugee-background student of Somali Bantu heritage employs linguistic resources to make sense of his experience with forced migration, resettlement, and formal education. Much of the educational research on refugee-background students (and other groups of English learners) propagates a deficit orientation in which educational gaps and challenges, rather than educational resources and potential, are the central focus. In contrast, this student's written and oral narratives construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 32 publications
2
55
0
2
Order By: Relevance
“…Through address and attribution, we get a glimpse of Zein described as “competent,” “funny,” and “creative” in relevance to his online bricolage. By unveiling these aspects of his identity, Zein helped dispel a deficit perspective of refugee ELs and added to an asset discourse (Shapiro & MacDonald, ) that highlights strength and agency. For example, he showed agency by asking his teacher to modify the language arts project (albeit the idea was initially suggested by me) to align it with his interests, possibilities of selfhood (Ivanič, ), and preferred language modality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Through address and attribution, we get a glimpse of Zein described as “competent,” “funny,” and “creative” in relevance to his online bricolage. By unveiling these aspects of his identity, Zein helped dispel a deficit perspective of refugee ELs and added to an asset discourse (Shapiro & MacDonald, ) that highlights strength and agency. For example, he showed agency by asking his teacher to modify the language arts project (albeit the idea was initially suggested by me) to align it with his interests, possibilities of selfhood (Ivanič, ), and preferred language modality.…”
Section: Discussionmentioning
confidence: 99%
“…If not addressed, such covert resistance can become a serious obstacle to learning and contribute to students’ disengagement. Through creating spaces where students can exercise their agency in using multimodal and multilingual forms of language, teachers can open the door to students like Zein to position themselves in an empowering manner and create counternarratives (Alvermann & Moore, ; Shapiro & MacDonald, ) that challenge deficit perspectives of refugee ELs. In short, classroom tasks with multimodal dimensions have the potential to transform resistance into engagement in classroom tasks in addition to providing opportunities for refugee students to share their (imagined) identities with their teachers and peers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Johnson () argued for a shift in how the field views success to encompass the complex ways in which African American youths in particular experience education. The growing number of studies that have demonstrated how urban youths use and reappropriate technology to create meaningful work represents such a counternarrative (e.g., Crampton, Scharber, Lewis, & Majors, ; Lewis Ellison, ; Shapiro & MacDonald, ).…”
mentioning
confidence: 99%